2019
DOI: 10.3390/cells8080843
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200-3p Is Potentially Involved in Cell Cycle Arrest by Regulating Cyclin A during Aestivation in Apostichopus japonicus

Abstract: The sea cucumber (Apostichopus japonicus) has become a good model organism for studying environmentally induced aestivation in marine invertebrates. We hypothesized that mechanisms that arrest energy-expensive cell cycle activity would contribute significantly to establishing the hypometabolic state during aestivation. Cyclin A is a core and particularly interesting cell cycle regulator that functions in both the S phase and in mitosis. In the present study, negative relationships between miR-200-3p and AjCA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Changing global climates are currently threatening their populations in northern China, forcing them to rapidly adjust to non-ideal higher summer temperatures, lower salinity and, of relevance to our review, limited oxygen availability (Plagányi et al, 2013;Huo et al, 2017). Previous work has examined the miRNA responses of sea cucumbers during estivation (see Glossary; Chen et al, 2013;Chen and Storey, 2014;Wang et al, 2019), and Huo and colleagues built on these results by using high-throughput sequencing to examine miRNA responses to hypoxia in the sea cucumber respiratory tree, an organ used for oxygen extraction (Huo et al, 2017). Of the 26 miRNAs differentially expressed (12 up-regulated and 14 down-regulated) during severe hypoxia, a subset are associated with hypoxia-adaptive mechanisms important for redox, transcription, small molecule and ion transport, and hydrolysis (Huo et al, 2017).…”
Section: The Role Of Oxymirs In Hypoxic Estuarine Habitats Sea Cucumbersmentioning
confidence: 99%
“…Changing global climates are currently threatening their populations in northern China, forcing them to rapidly adjust to non-ideal higher summer temperatures, lower salinity and, of relevance to our review, limited oxygen availability (Plagányi et al, 2013;Huo et al, 2017). Previous work has examined the miRNA responses of sea cucumbers during estivation (see Glossary; Chen et al, 2013;Chen and Storey, 2014;Wang et al, 2019), and Huo and colleagues built on these results by using high-throughput sequencing to examine miRNA responses to hypoxia in the sea cucumber respiratory tree, an organ used for oxygen extraction (Huo et al, 2017). Of the 26 miRNAs differentially expressed (12 up-regulated and 14 down-regulated) during severe hypoxia, a subset are associated with hypoxia-adaptive mechanisms important for redox, transcription, small molecule and ion transport, and hydrolysis (Huo et al, 2017).…”
Section: The Role Of Oxymirs In Hypoxic Estuarine Habitats Sea Cucumbersmentioning
confidence: 99%
“…The sulfated polysaccharide isolated from sea cucumber Stichopus japonicus on the 6-hydroxydopamine-induced apoptosis in SH-SY5Y cells (a human dopaminergic neuroblastoma cell line) significantly elevated protein levers of Cyclin D3 [47]. It has been reported that, in sea cucumber (Apostichopus japonicus), regulating Cyclin A could arrest cell cycle progression [48]. In HepG2, A549, and Panc02 cells, the effects of the distribution of cell cycle by H. leucospilota protein may be associated with several cyclins, cyclin-dependent kinases and other regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that p53 mediates oxidative stress in cells with irreparable DNA damage, and induces apoptosis in concert with other apoptotic proteins e.g., Bax ( Hori et al, 2013 ). The combination of cyclin A and CDK2 or CDK1 regulates S phase and mitosis ( Wang et al, 2019b ). Cyclin E-CDK2 complex regulates the duplication of intracellular chromosomes which promote the entry of cells into the S phase, and on entering the G2 phase, there is a gradual decrease in cyclin E content ( Shang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, HL-7702 cell viability was increased after treatment with ginsenoside Rb1, indicating, significant attenuation of TP-induced cytotoxic effect on the cells. Apoptosis is triggered by exogenous and endogenous pathways, and the caspase family plays a crucial role in both pathways (Shao et al, 2019;Wang et al, 2019b). Fas is one of the most typical death receptors in the exogenous death receptor- (Xu et al, 2020).…”
Section: Effect Of Ginsenoside Rb1 On Triptolide-induced Mitochondrial Dysfunction In Hl-7702 Cellsmentioning
confidence: 99%